A Study of Training Preferences in Rice Cultivation in Jammu District of J&K State - Kumar, Yogesh; Nain, M. S. (Indian Journal of Extension Education, 2013)
Ever increasing population poses production needs of 140 million tonnes of rice per year by 2025 requiring higher  management practices. This demands increased emphasis on need based training of farmers in rice production  technology. The present study was undertaken in Jammu district of J&K state to delineate the farmers' training need in rice  production. The study was conducted on 80 randomly selected farmers of R.S. Pura block with a pre-structured interview  schedule. The findings revealed that the farmers were requiring training in almost all the subject matter areas of rice  production specially use of insecticides, pesticides, use of manures and fertilizers, seed and seed technology and water  management.
Keywords: Rice production technology; training needs